NO2 sensing properties of flame-made MnOx-loaded ZnO-nanoparticle thick film - Tamaekong,N. (Elsevier, 2015)
In this work, unloaded and 0.25-1.00 mol% MnOx-loaded ZnO nanoparticles synthesized by a single step flame spray pyrolysis are systematically investigated for NO2 sensing. Structural characterizations revealed hexagonal-phase polycrystalline ZnO nanoparticles with nominal diameter of 5-15 nm were uniformly decorated with ultra fine MnOx nanoparticles with 0.5-2 nm in diameter. In addition, it was found that specific surface area increased and the average decreased monotonically with increasing MnOx concentration from 0 to 1.0 mol%. Gas sensing studies clearly demonstrated that MnOx loading on ZnO nanoparticles led to significant enhancement of NO2 sensing performances in terms response and selectivity. The optimum MnOx concentration was found be 0.25 mol% and 0.25 mol% MnOx-loaded ZnO sensor exhibited a high NO2 response of ∼2700 for NO2 concentration of 50 ppm in dry air at 350 °C. In addition, it exhibited good selectivity against NH3 and H2S gases. © 2014 Elsevier B.V.